MOTIVES AND SATISFACTION OF INDONESIAN WOMEN IN WATCHING THAI SERIES “KINNPORSCHE THE SERIES” - Azzahra, Annisa Nursabrina; Esfandari, Diah Agung (Jurnal Komunikasi dan Bisnis, 2023)
The internet does not only impact communicating media, but broadcast media is also affected by the emergence of internet-based broadcasting platforms. Through this platform, audiences can watch foreign shows with various genres, including the boys' love genre, such as KinnPorsche The Series, which comes from Thailand. This study aims to determine the motives and satisfaction of Indonesian female audiences in watching the boys' love series "KinnPorsche The Series." Researchers use the Uses and Gratification theory with four indicators: entertainment, social integration and interaction, personal identity, and information. This type of research is quantitative research with online survey research methods. The data analysis technique used is quantitative descriptive analysis. The results of this study show that the highest motives and satisfaction are on the entertainment indicators, and the lowest is on the integration and social interaction indicators. Female viewers get satisfaction in indicators of integrity and social interaction, personal identity, and information, and do not get satisfaction in entertainment indicators. Although the entertainment indicator has the highest motive value and satisfaction, it is not satisfied. Thus, subsequent researchers should analyze what factors make the entertainment indicator occupy the highest value.